2016
DOI: 10.1373/clinchem.2016.263475
|View full text |Cite
|
Sign up to set email alerts
|

Free and Glucuronide Whole Blood Cannabinoids' Pharmacokinetics after Controlled Smoked, Vaporized, and Oral Cannabis Administration in Frequent and Occasional Cannabis Users: Identification of Recent Cannabis Intake

Abstract: BACKGROUND There is increasing interest in markers of recent cannabis use because following frequent cannabis intake, Δ9-tetrahydrocannabinol (THC) may be detected in blood for up to 30 days. The minor cannabinoids cannabidiol, cannabinol (CBN), and THC-glucuronide were previously detected for ≤2.1 h in frequent and occasional smokers' blood after cannabis smoking. Cannabigerol (CBG), Δ9-tetrahydrocannabivarin (THCV), and 11-nor-9-carboxy-THCV might also be recent use markers, but their blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
120
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 24 publications
7
120
2
Order By: Relevance
“…In contrast to similar clearance estimates between this study and that of Heuberger et al ., our estimate of V SS (sum of V1, V2 and V3) was 3401 L and was considerably larger than their estimate of 236 L. Using the THC typical value parameters in Table , the estimated terminal phase half‐life for THC is calculated to be approximately 3.5 days, indicating its distribution to deep, presumably lipid tissues. Despite the reliance of only a few data points near the low limit of quantification near the terminal slope (Figure ), this estimate is consistent with the persistence of THC and observed similar half‐lives after cessation of chronic cannabis use …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast to similar clearance estimates between this study and that of Heuberger et al ., our estimate of V SS (sum of V1, V2 and V3) was 3401 L and was considerably larger than their estimate of 236 L. Using the THC typical value parameters in Table , the estimated terminal phase half‐life for THC is calculated to be approximately 3.5 days, indicating its distribution to deep, presumably lipid tissues. Despite the reliance of only a few data points near the low limit of quantification near the terminal slope (Figure ), this estimate is consistent with the persistence of THC and observed similar half‐lives after cessation of chronic cannabis use …”
Section: Discussionsupporting
confidence: 81%
“…Despite the reliance of only a few data points near the low limit of quantification near the terminal slope (Figure 4), this estimate is consistent with the persistence of THC and observed similar half-lives after cessation of chronic cannabis use. 12,16,22 From the perspective of plasma sampling we estimated that 74% of inhaled THC is metabolized to 11-OH-THC. This percentage should be viewed as the minimum amount of THC converted first to 11-OH-THC as models of hepatic metabolism estimated from plasma samples model only the 11-OH-THC that circulated in the blood before returning to the liver for subsequent metabolism to THCCOOH or other products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design was within‐subject, randomized, double‐blind, double‐dummy, and placebo‐controlled, with each participant receiving the active drug by all three routes of administration and placebo oral and inhaled doses within four sessions as previously described . In each session, participants ingested a brownie (Duncan Hines ® Double Fudge brownie mix) and either smoked a cigarette or inhaled from a vaporizer (210°C, Volcano Medic, Storz & Bickel).…”
Section: Methodsmentioning
confidence: 99%
“…Newmeyer et al conducted a placebo‐controlled, within‐subject, randomized study of eight chronic frequent and eight occasional cannabis users following administration of a single 50.6 mg THC dose by oral, smoked, and vaporized routes . This published study examined blood concentrations and reported free and glucuronide cannabinoid concentrations as well as pharmacokinetic parameters.…”
Section: Introductionmentioning
confidence: 99%